The Relationship of Factors Influencing Behavioral Intention to Participate in Hybrid Education: Undergraduate University Students Majoring in English, Chengdu, China - Zou, Xiaoyi; Limpapath, Pimurai (LEARN Journal: Language Education and Acquisition Research Network, 2024)
The purpose of this study was to investigate the relationship of factors influencing behavioral intention to participate in hybrid education of undergraduate university students majoring in English in Chengdu Universities, China. Questionnaires were collected with 450 respondents from three public universities in Chengdu with the reliability (Cronbach Alpha Coefficient) of 0.918. Confirmatory Factor Analysis (CFA) was run to identify the factors influencing behavioral intentions to participate in hybrid education. Subsequently, Structural Equation Modeling (SEM) was used to ascertain the causal relationships between factors. It was found that perceived usefulness, perceived ease of use, and perceived convenience indirectly influenced behavioral intention to participate in hybrid education and was mediated by attitude towards use with the direct impact of social influence and effort expectancy on behavioral intention. It is expected that, the model of the relationship of factors influencing behavioral intention to participate in hybrid education created in this study would be beneficial for undergraduate students majoring in English, in Chengdu Universities or alike, to achieve their goals in learning English both online and onsite effectively.